The Moderna exhibition 2006 : When am I ? = Moderna utställningen 2006. - Malm, Magdalena; Nilsson, John Peter (Stockholm : Moderna Museet Stockholm, 2006)
Andersson, Christian ; Andersson, Henrik ; Andersson, Karin Mamma ; Andersson, Torsten ; Astrand, Ola ; Bäckström, Miriam ; Bärtas, Magnus ; Billing, Johanna ; Böttcher, Ann ; Carlsson, Camilla ; Cherinet, Loulou ; Dahlberg, Jonas ; Dahlgren, Jacob ; Djurberg, Nathalie ; Edefalk, Cecilia ; Enoksson, Per ; Eriksson, Andreas ; Eriksson, Annika ; Eriksson, Elis ; Fabra, Juan-Pedro ; Gmelin, Felix ; Hafström, Jan ; Hansson, Ronny ; Hasselberg, Per ; Hausswolff, Annika von ; Hjelm, Mats ; Holmkvist, Saskia ; Jeannin, Lisa ; Kallioinen, Matti ; Kjellgren, Jonas ; Klingberg, Gunilla ; Korsar, Oskar ; Larsson, Annika ; Lindberg de Geer, Marianne ; Magnusson, Jenny ; Marc, Dorinal ; Marklinger, Monika ; Mozard, Tova ; Namazi, Sirous ; Nobel, Jonas ; Ogland, Ylva ; Pehrson, Ola ; Ridel ; Sandlund, Fia-Stina ; Sjolund, Stig ; Tedsdotter, Linda ; Thierfelder, Magnus ; Thurfjell, Johan ; Wallin, Magnus ; Wessman, Anna
biog., geselect. ind. & gr. tent. p. 326-330
Engels
Zweeds
Exhibition. The Moderna exhibition 2006 : When am I ? = Moderna utställingen 2006. Moderna Museet Stockholm. 2006-03-01. 2007-04-01
boek
Keywords: Stockholm